Opuntia leoglossa sp. nov. (Cactaceae): a new identity for the aloctone “Lion’s Tongue” cactus - Köhler, Matias; Font, Fabián (Phytotaxa, 2021)
Recent studies have shown that a worldwide cultivated plant known as “Lion’s Tongue” has been historically and wrongly assigned to another taxon name (Opuntia schickendantzii). After a literature study and the examination of herbarium specimens, we propose to describe the “Lion’s Tongue” as Opuntia leoglossa sp. nov. Although a hybrid origin or artificial selection is speculated, further studies must be carried out to better understand this taxon which has a hitherto unknown origin.